A comparative study between the information retrieval systems MyLegalWhiz, Westlaw, and CDAsia based on focus group discussions among the students of UP College of Law, and Ateneo Law School - Llorito, Ovid Exequiel D.; Mallonga, Maria Andrea Q. (Quezon City School of Library and Information Studies, University of the Philippines, 2016)
Information Retrieval Systems are tools used by those in the legal profession to help thm locate legal information for their information needs. This study aimed to find out the differences between th einformation retrieval systems MyLegalWhiz, Westlaw and CDAsia from the opinions fo law school students. Nine students from Ateneo Law School and six students from the UP College of Law were asked to participate in two focus group discussions to answer the study's research questions. A third focus group discussion was planned with the students of San Beda College of Law as the respondents, but did not push through due to lack of time and scheduling difficulties. Students from the UP College of Law used Lex Libris and HeinOnline as their primary IRS, compared to Ateneo law school students group who used eSCRA as well as virtual law libraries Chan Robles and Lawphil.net. UP law students had the tendency to use only a single information retrieval system compared to Ateneo law students who used multiple ones. The usage of information retrieval systems by UP law students as well as the Ateneo law students were influenced by their professors, as well as other factors such as familiarity with said information retrieval systems, personal preferences. Ateneo law school students picked eSCRA as their best choice information retrieval system, compared to UP law students who picked Lex Libris. Finally, Ateneo law school students predicted the advanced information retrieval systems of the future will have integrated features, as well as the ability to think like human beings, while UP law students predicted that as a information retrieval systems improve, prices will go down, but may cause increased privatization of the legal resources by the private sector, which might cause a disincentive for the government's judiciary branch to publish legal materials themselves.
Undergraduate thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman.
Keywords: Law libraries -- Electronic information resources -- Philippines -- Quezon City; Electronic information resource searching -- Philippines -- Quezon City; Information retrieval -- Computer programs